2022
DOI: 10.1002/ams2.772
|View full text |Cite
|
Sign up to set email alerts
|

Insulin overdose complicated by treatment‐induced acute hepatic steatosis in a nondiabetic patient

Abstract: Background There are few reports of dextrose‐associated hepatic steatosis during insulin overdose treatment. Reports in nondiabetic patients are extremely rare. There is inadequate knowledge about the clinical course and treatment. Case Presentation A 37‐year‐old previously healthy, nondiabetic man self‐administered 5,925 IU of insulin. On admission, his liver function tests were normal. However, following continued dextrose treatment, they increased, and he was diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hepatic ADRs are being increasingly reported in clinical data and EHRs, and they certainly represent a diagnostic and therapeutic challenge. However, it is prudent to mention that several studies have reported-hepatic injury associated with insulin treatment or overdose, is likely due to glycogenesis rather than inherent liver injury from the insulin usage 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic ADRs are being increasingly reported in clinical data and EHRs, and they certainly represent a diagnostic and therapeutic challenge. However, it is prudent to mention that several studies have reported-hepatic injury associated with insulin treatment or overdose, is likely due to glycogenesis rather than inherent liver injury from the insulin usage 14,15 .…”
Section: Discussionmentioning
confidence: 99%